2022
DOI: 10.1136/rmdopen-2021-001939
|View full text |Cite
|
Sign up to set email alerts
|

What amount of structural damage defines sacroiliitis: a CT study

Abstract: ObjectivesTo propose a data-driven definition for structural changes of sacroiliac (SI) joints in the context of axial spondyloarthritis (axSpA) imaging on a large collective of CT datasets.Methods546 individuals (102 axSpA, 80 non-axSpA low back pain and 364 controls without back pain) with SI joint CTs were evaluated for erosions, sclerosis and ankylosis using a structured scoring system. Lesion frequencies and spatial distribution were compared between groups. Diagnostic performance (sensitivity (SE), speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
3
7
0
2
Order By: Relevance
“…Another interesting finding of possible relevance in this context was reported recently when investigating which structural SI lesions on CT performed best for the diagnosis of axSpA 27. For this, the SI joint was segmented in ventral, middle and dorsal parts, and it was found that the presence of erosion and ankylosis differentiated best between axSpA and non-SpA; however, this was the case only for the middle and dorsal parts and not for the ventral regions of the joint that are typically prone to mechanical stress.…”
Section: Do We Have Enough Data To Define Sacroiliitis Based On Struc...mentioning
confidence: 69%
“…Another interesting finding of possible relevance in this context was reported recently when investigating which structural SI lesions on CT performed best for the diagnosis of axSpA 27. For this, the SI joint was segmented in ventral, middle and dorsal parts, and it was found that the presence of erosion and ankylosis differentiated best between axSpA and non-SpA; however, this was the case only for the middle and dorsal parts and not for the ventral regions of the joint that are typically prone to mechanical stress.…”
Section: Do We Have Enough Data To Define Sacroiliitis Based On Struc...mentioning
confidence: 69%
“…10 Discordant reporting particularly occurs for grade 1 and grade 2 sacroiliitis changes according to the mNY criteria, 6 10 11 and the highest concordance reporting rates are for definitely normal (grade 0) or definitely abnormal (grade 4) SIJs. 10 Of the mNY grading criteria, erosions, which are highly specific axSpA lesions, 12 were found to have the lowest interreader agreement (25%). 11 The misinterpretation of patients with grade 2 sacroiliitis may have diagnostic and therapeutic consequences because bilateral grade 2 changes represent a positive radiograph for sacroiliitis ( Table 1 ).…”
Section: Part 1: Current Role Of Radiography For Sacroiliitis In Adultsmentioning
confidence: 98%
“…Prinzipiell wird zwischen aktiven und strukturellen Läsionen bei der Bildgebung der Sakroiliakalgelenken unterschieden. Strukturelle Läsionen treten typischerweise etwas später im Verlauf der Erkrankung auf und haben eine höhere Spezifität [2,3] -in diese Gruppe fallen insbesondere Erosionen der Gelenkflächen sowie knöcherne Neubildungen, wie die Ankylose oder der Vorläufer der Ankylose -Reparaturgewebe in der Erosionshöhle, auch als "Backfill" bezeichnet [4]. Aktive Läsionen zeigen entzündliche Floridität an; die wichtigste aktive Läsion ist das Knochenmarködem, das auch als Osteitis bezeichnet wird und sich durch eine Steigerung des Flüssig-keitssignals des Knochenmarks in der MRT angrenzend an den Gelenkspalt auszeichnet.…”
Section: Zusammenfassungunclassified
“…Hierbei ist insbesondere die Lokalisation der Läsionen von entscheidender Bedeutung: Nicht nur ist das ventrale Gelenkdrittel der typische Manifestationsort der Osteitis condensans ilii 7 , sondern auch anderer mechanischer Erkrankungen der Sakroiliakalgelenke 19 . Hieraus ergibt sich eine Verbesserung der diagnostischen Performance der CT, wenn das vordere Gelenkdrittel nicht mit in die Analyse einbezogen wird 2 und in der klinischen Praxis sollte bei ausschließlich ventral lokalisierten Läsionen, insbesondere bei Frauen, die Diagnose einer axialen Spondyloarthritis kritisch hinterfragt werden. Neben diesen eher differenzialdiagnostischen Überlegungen existieren jedoch auch wesentliche Geschlechtsunterschiede im radiologischen Erscheinungsbild der axialen Spondyloarthritis am Sakroiliakalgelenk.…”
Section: Geschlechtsunterschiede In Der Bildgebung Der Sakroiliakalge...unclassified